Multi-criteria decision-making methods – applications in textile and apparel industry - (:unkn) unknown (My University, 2023)
Decision-making is an important concept that we encounter in many subjects from meeting a simple need to choosing the location of a factory. So much so that regardless of gender, profession, educational status or income status, it is an activity that every person performs in almost every subject, in all processes from daily life to business life. Due to this importance, the issue of decision-making has been the focus of attention of researchers from past to present and different studies have been carried out in almost every field on this subject. Since multi-criteria decision-making is a wide subject, in this chapter, only decision-making (DM), types of DM, DM situations and elements, factors affecting DM, DM process, Multi-Criteria Decision-Making (MCDM) and MCDM techniques and the applications of these techniques in apparel and textiles are included.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)